2020
DOI: 10.1021/acs.joc.0c02158
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nucleic Acid with Double Face: Homothymine–Homocytosine Bimodal Cα-PNA (bm-Cα-PNA) Forms a Double Duplex of the bm-PNA2:DNA Triplex

Abstract: Cα-bimodal peptide nucleic acids (bm-Cα-PNA) are PNAs with two faces and are designed homologues of PNAs in which each aminoethylglycine (aeg) repeating unit in the standard PNA backbone hosts a second nucleobase at Cα through a spacer chain with a triazole linker. Such bm-Cα-PNA with mixed sequences can form double duplexes by simultaneous binding to two complementary DNAs, one to the base sequence on t-amide side and the other to the bases on the Cα side chain. The synthesis of bm-Cα-PNA with homothymine (T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…Column chromatography was performed with Silica Gel 60 (particle size 0.040-0.063 μm, Merck). 1 H NMR, 13 C NMR, 19 F NMR and 31…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Column chromatography was performed with Silica Gel 60 (particle size 0.040-0.063 μm, Merck). 1 H NMR, 13 C NMR, 19 F NMR and 31…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several double-headed nucleoside designs have been presented in the literature. [7][8][9][10][11][12][13] Our previous work has shown that depending on the site of attachment, the additional nucleobase can be positioned in the minor groove, [14][15][16][17] the major groove, [18][19][20] or the center of a DNA duplex. [21][22][23] In the latter case, given that the additional nucleobase is linked through a methylene to the 2'-position of 2'-deoxyuridine or arabinouridine (Figure 1, U X ), the doubleheaded nucleotide has been shown to behave as a condensed dinucleotide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have also investigated positively charged α-and γ-modifications of the PNA backbone, and most of them showed promising hybridization properties and improved cellular uptake [82][83][84][85][86]. Very recent work has used α-and γ-positions of the PNA backbone to attach additional nucleobases, which enable these "double face" PNAs to form higher order double and triple helical structures [87,88].…”
Section: Conformationally Constrained Backbonesmentioning
confidence: 99%